Design of encrypted transceiver Non-coherent OFDM with ability to correct coding bits of information - Kareem J. Thajeel; Izz K. Abboud; Laith A. Kunbar (Institute of Advanced Engineering and Science, 2019)
A differential encrypted transceiver was designed in the signal-to-noise ratio systems. A time